2020
DOI: 10.3832/ifor3394-013
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of forests across Italy: an exploratory national survey

Abstract: In a context of progressive expansion of the Italian forest area, we present the results of a national survey exploring public perception of forests across different geographical scales in Italy. Perceptions of forests are assessed in relation to popular beliefs on relevant environmental issues such as countering climate change, protecting biodiversity, and promoting social cohesion and environmental education. Participants (N = 1059) living in five different regions of Northern (Trentino-Alto Adige/Südtirol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Thus far, empirical studies of connectedness to nature have mainly centered on closeness with actual forests [e.g., ( 93 )] and urban greenspaces [e.g., ( 94 )]. The present study echoes findings of previous studies, that virtual or simulated nature ( 95 , 96 ) can be one source of human connectedness to nature, as we found that people who intended to expose themselves to virtual nature had a higher connectedness with nature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, empirical studies of connectedness to nature have mainly centered on closeness with actual forests [e.g., ( 93 )] and urban greenspaces [e.g., ( 94 )]. The present study echoes findings of previous studies, that virtual or simulated nature ( 95 , 96 ) can be one source of human connectedness to nature, as we found that people who intended to expose themselves to virtual nature had a higher connectedness with nature.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in previous studies, changes in perception towards forests and shifts in societal values have influenced local communities' preferences for ecosystem services. Carrus et al [128] reported that people in modern society are increasingly recognizing the ecological and social values of trees and forests. Consequently, among various forest ecosystem services, biodiversity is the most preferred.…”
Section: Private Forest Ecosystem Servicesmentioning
confidence: 99%
“…The studies conducted within the domain of environmental psychology have confirmed the link between well-being and life satisfaction with the contact with nature [ 6 ] The role of nature for human health and well-being is an undeniable fact [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%